LEGAL PROTECTION FOR CHILDREN AS PERPETRATORS AND VICTIMS OF CRIME: A STUDY OF THE IMPLEMENTATION OF LAW NUMBER 11 OF 2012 CONCERNING THE JUVENILE CRIMINAL JUSTICE SYSTEM - Yogi Apriansyah; Adistya Sunggara (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This journal is written solely as an effort to provide solutions in providing legal protection for children in conflict with the law, either as perpetrators or as victims and witnesses in criminal acts. Such thinking arises because the implementation of Law Number 11 of 2012 cannot be fully implemented even though the Law has provided clear concepts in handling cases of children in conflict with the law while still paying attention to legal protection for children. In order to obtain a measurable analysis related to the problems that arise in the implementation of child protection and to find solutions to these problems, the author uses a normative legal research method with an analytical approach to legal synchronization and analysis of principles. The use of this method directs the author to be able to provide analysis and describe the problems of implementing legal protection for children in conflict with the law and describe the solutions in writing this journal.